LINX I and II: Lessons Learned and Emerging Questions - Wymore, Adam S.; Rodríguez-Cardona, Bianca M.; Herreid, Allison; McDowell, William H. (Frontiers in Environmental Science, 2019)
Anthropogenic nitrogen (N) loading has had widespread effects on the integrity of aquatic ecosystems. Headwater streams play a central role in controlling watershed N budgets by serving as a final environmental filter for excess nutrient inputs before they are exported to downstream receiving waters. Understanding the controls on in-stream N cycling has direct implications for water quality; however, in-stream nitrogen cycling is also a source of greenhouse gas production including nitrous oxide (N2O). Here we review some lessons learned from the Lotic Intersite Nitrogen eXperiments (LINX I and II), which were a series of replicated 15N in situ manipulations across biomes and land-uses designed to provide insight into the controls and fate of inorganic nitrogen in stream ecosystems. We highlight six unique insights gained from these continental- scale projects and discuss their implications for predicting fluxes and concentrations of N2O through a series of emerging questions to motivate future work. Our objective in this review is to present both retrospective and forward-looking perspectives on the N cycle in headwater streams and river networks.